Kerjasama Antar Daerah Dalam Pengolahan Akhir Sampah Di Wilayah Metropolitan Bandung Raya Provinsi Jawa Barat - Â Shafiera Â Amalia (Center fo State Civil Apparatus Training and Development and Competency Mapping, 2014)
This research described about intergovernmental cooperation between West lava Province, and Region/Municipalities in Bandung Raya Metropolitan Area. The subject cooperation is waste ï¬nal processing. The aims of this research are to describe about authority sharing; organization structure; management; and budget from intergovernmental cooperation practice. This Research used qualitative approach and descriptive method. Interview Technique was used to collect primary data. And purposive technique was used to choose the right informan for this research. Furthermore, this research used qualitative dacriptive technique to analyse data. The result showed that West lava Province roleas Regional Final Disposal Site (TPPAS Sarimukti) provider and Region/Municipalities in Bandung Raya Metropolitan Area role as user that ï¬nal disposal site. Waste from Region/Municipalities in Bandung Raya Metropolitan Area are proassed in that ï¬nal disposal site. West lava Province facilitated UPTD Balai Pengelolaan Sampah Regional (BPSR) establishment to manage that Final Disposal Site. Meanwhile, Sarimukti Final Disposal Site budget derived ï¬om sharing between West lava Province, and Region/Municipalities in Bandung Raya Metropolitan Area. So far, waste final processing cooperation eï¬‚ï¬ctively run and really help Region and Municipalities in Bandung Raya Metropolitan Area in processing their waste.